Vaginal Cleansing Practices in HIV Infected Zambian Women - Alcaide, Maria L. (2013)
Vaginal practices are a variety of behavioral techniques that women use to manage their sexual life and personal hygiene. Women perceive vaginal practices as a beneficial practice. However, vaginal cleansing has been identified as one of the main risk factors for bacterial vaginosis and is potentially implicated in Human Immune Deficiency Virus (HIV) and sexually transmitted infection transmission. This study examined the prevalence of vaginal practices and the types of practices used among a sample of HIV positive women living in Lusaka, Zambia. Over 90% of all women recruited engaged in vaginal practices. Certain practices, such as use of water or soap, were more frequently used for hygiene reasons. Herbs and traditional medicines were mainly used to please sexual partner. Strategies to decrease VP appear urgently needed in the Zambian community.